2021
DOI: 10.5194/wes-2021-96
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A computationally efficient engineering aerodynamic model for swept wind turbine blades

Abstract: Abstract. In this work, a computationally efficient engineering model for the aerodynamics of swept wind turbine blades is proposed for the extended blade element momentum (BEM) formulation. The model is modified based on a coupled near- and far-wake model, in which the near-wake is assumed to be the first quarter revolution of the non-expanding helical wake of the own blade. For the special case of in-plane trailed vorticity, the original empirical equations determining the steady-state value of the near-wake… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…A similar pattern of spanwise load redistribution was also observed for swept blades in the previous works (Li et al, 2018(Li et al, , 2020(Li et al, , 2021. However, the redistribution of the loads only takes place where the blade is swept.…”
Section: Dihedral Blade With Zero Conesupporting
confidence: 82%
See 1 more Smart Citation
“…A similar pattern of spanwise load redistribution was also observed for swept blades in the previous works (Li et al, 2018(Li et al, , 2020(Li et al, , 2021. However, the redistribution of the loads only takes place where the blade is swept.…”
Section: Dihedral Blade With Zero Conesupporting
confidence: 82%
“…In the present work, only the out-of-plane shape of the blade is considered, which means the blade is assumed to have no in-plane sweep. The engineering aerodynamic model for the blades with only in-plane shapes is described by Li et al (2021). The structure of the work is as follows: the Kutta-Joukowski analysis of the non-planar rotor is performed in Sect.…”
mentioning
confidence: 99%
“…There are, however, situations that involve the induced velocities throughout the rotor plane rather than just along straight LLs. An example is a swept rotor, with the LL curved in the plane of rotation, which has been the subject of a significant amount of recent research, e.g., Fritz et al (2022), Li et al (2022b), and Gemaque et al (2022). The first two studied swept wind turbine blades using different approximations for the induced velocities.…”
Section: Woodmentioning
confidence: 99%
“…The first two studied swept wind turbine blades using different approximations for the induced velocities. Fritz et al (2022) used a restricted version of the analysis developed here, whereas Li et al (2022b) used a vortex-cylinder model of the wake. It is suggested that the present analysis is simpler and more general.…”
Section: Woodmentioning
confidence: 99%